Strategic direction: Projection of technological innovation and administrative management in small enterprises (2017)
The main objective of this research is to establish the level of innovation in technology and strategic direction of small and medium size enterprises (SMEs) in the city of Barranquilla, Colombia. For this purpose, a descriptive research was carried out, using a data collection technique, which analyzed six variables that determined the size of the company in terms of number of workers, the type of innovative activities they implement, the budget that invest in technology, the preferences in the area in which they innovate and the existing relationships between what they invest and the technological innovations carried out in a sample of ten companies of the city. The results of this exercise show that more than half of the companies belonging to the sample are medium-sized enterprises, and only 40% of them develop activities focused on technological innovation, preferably involving marketing and design actions, investing quantities that are reflected in the organizational development.